Fire effects on a Spartina densiflora salt marsh in the floodplain of the Paraná River, Argentina - Madanes, N. (2007)
We studied the effects of fire on the structural attributes of a Spartina densiflora salt marsh. The study was carried out from November 1995, spring (N95S) to December 1996, late spring (D96LS). In November 1995, we installed 37 permanent plots. In January 1996, 32 of the plots were accidentally burned (B) and the remaining were not burned (NB). Vegetation on each plot was sampled seasonally, plant species were identified and cover-abundance was estimated. We analyzed and compared seasonal variations in plant species richness, diversity, composition and cover-abundance in burned and non-burned plots. In addition, we analyzed variations in biological types (forbs, graminoids) and types of life cycles (annuals, perennials) in B and NB plots before and after the fire .Principal Component Analysis (PC A) was performed on cover-abundance data for each treatment and sampling date. We included coded dummy variables for each date and treatment as supplementary variables. Results indicated that S. densiflora was the dominant species and Limonium brasiliensis and Dipsacum fullonum were the accompanying species for all treatments and sampling dates. Thirty out of 47 species were present before the fire (N95S). All species in NB plots were also recorded in B plots, and 15 species were exclusively found in B plots. The increases in species richness and diversity observed in B plots after the fire were higher than those in NB plots at the same sampling dates. When comparing the B plots before and after the fire, perennials decreased in cover-abundance and increased in richness, while both attributes increased for annuals; the same pattern was followed by forbs, and graminoids decreased in cover abundance and showed almost similar values of richness. PCA results showed that NB plots were subject to smooth temporal changes in composition and cover abundance, and that B plots underwent greater changes. In D96LS, B and NB plots exhibited a different spatial distribution, which in turn differed from that observed in pre-fire plots in N95S. © 2007 Sociedad de Biología de Chile.